A pilot study comparing parent and adolescent online health information seeking behaviours in elective pediatric surgical situations - Wong, Sophia S.M.; Wong, Kenneth P.L.; Angus, Mark I.L.; Chen, Yong; Choo, Candy S.C.; Nah, Shireen Anne (Springer Verlag, 2020)
Purpose: Little is known of how children seek health information. This study evaluates online health information (OHI) seeking behaviours in adolescents undergoing major elective surgical procedures and compares responses within parent–child dyads. Methods: With institutional approval, we prospectively surveyed parents of children admitted to our institution for major elective operations between November 2017 and November 2018, using convenience sampling. Patients aged 12 years and above were also invited. Each respondent completed an anonymized modification of a previously published survey on Internet usage. Chi squared tests were used for categorical data, with significance at P value < 0.05. Results: Ninety-one parents and 19 patients (median age 15 years, range 12–18) responded, with 13 parent–child pairs. Daily Internet access was reported by 84 (93%) parents and 18 (95%) children, but OHI was sought in 77% of parents and 74% of children. Six (32%) children could not name their admitting condition, compared to 10 (11%) parents. Nine (50%) children consulted family and friends for information compared to 27 (30%) parents. Parents were more likely to access hospital websites (n = 15, 44%) compared to no children (p = 0.01), while most children (n = 7, 70%) accessed non-health websites (e.g. Wikipedia). In the 13 parent–child pairs, only one parent accurately assessed what their child understood of their condition. Most patients (63.6%) did not understand the aspects of their condition that their parents deemed important. Conclusions: This study highlights the differences in parental and child behaviours. Children are equally important to include when counselling. Surgeons can guide both parties to reliable Internet sources for health information. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.